Preparation method of polymer microporous material
By using EVOH materials and optimizing the preparation process, the problems of insufficient hydrophilicity and limited structural control in environmental applications of polymer microporous materials are solved, and microporous materials with excellent hydrophilicity and mechanical properties are prepared, which are suitable for water treatment and environmental protection fields.
Patent Information
- Application Number
- CN202411630726.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-07
AI Technical Summary
Existing polymer microporous materials have insufficient hydrophilicity and limited structural control in environmental applications, making them difficult to be efficiently used in water treatment and liquid filtration applications.
Ethylene-vinyl alcohol copolymer (EVOH) is used as the substrate, and the formation of microporous structures is controlled by the selection of solvents and the optimization of the phase separation process to prepare microporous materials with excellent hydrophilicity and mechanical properties.
It significantly improves the hydrophilic properties of the material, realizes the controllability of the microporous structure, ensures the mechanical strength and stability of the material, and is suitable for water treatment and environmental protection fields.
Smart Images

Figure CN119570104A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the research field of polymer microporous materials, and in particular to a preparation method of polymer microporous materials. Background Art
[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.
[0003] Polymer microporous materials have been widely used in liquid separation, gas filtration, wastewater treatment, biomedicine and other fields due to their advantages such as light weight, stable structure and relatively low cost. However, the current polymer microporous materials mainly include olefin materials such as polypropylene (PP) and polyethylene (PE), as well as fluorinated polymers such as polytetrafluoroethylene (PTFE). Although these materials have good mechanical strength and chemical stability, they are not hydrophilic in nature and are difficult to meet the application requirements of specific environments such as water treatment. Therefore, during use, it is often necessary to modify the surface to improve the hydrophilicity of the material, which not only increases the preparation cost, but may also affect the permeability and durability of the material.
[0004] In contrast, ethylene-vinyl alcohol copolymer (EVOH) has a large number of hydroxyl groups in its molecular structure and has natural hydrophilic properties, which can effectively promote the penetration and adsorption of water. EVOH materials have been widely used in the field of packaging barrier materials due to their excellent performance in gas barrier, but the application potential of microporous materials prepared by them in the fields of environmental protection, water treatment, filtration and classification has not been fully developed. In these fields, the hydrophilicity and structural characteristics of microporous materials will directly affect their performance and application effects.
[0005] Although EVOH materials have significant advantages in hydrophilicity and chemical stability, there is relatively little research on the preparation and control of their microporous structure. In particular, there is still much room for research on how to regulate the microporous structure through the preparation process to meet different application requirements. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a polymer microporous material in view of the problem that the current polymer microporous materials are insufficiently hydrophilic and have limited structural control in environmental applications, making them difficult to be used efficiently in water treatment and other liquid filtration applications. Ethylene vinyl alcohol polymer (EVOH) is used as a substrate, and the formation of the microporous structure is controlled by selecting a solvent and optimizing the phase separation process, thereby finally obtaining a microporous material with excellent hydrophilicity and mechanical properties. This EVOH microporous material has excellent application prospects in the fields of liquid separation and wastewater treatment, and has opened up a new direction for it in the fields of environmental protection and water treatment.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a polymer microporous material, comprising:
[0009] Step S1: preparing a coating liquid based on ethylene vinyl alcohol polymer EVOH particles and a solvent;
[0010] Step S2: degassing the coating liquid;
[0011] Step S3: coating the degassing coating liquid on the glass plate;
[0012] Step S4: placing the coated glass plate into a coagulation bath for phase separation, and removing the diaphragm;
[0013] Step S5: After the separator is completely dried, a white EVOH microporous membrane is obtained.
[0014] Furthermore, the solid content of the coating liquid is 10-30%.
[0015] Furthermore, the solvent is one of DMSO, NMP or NPA / H2O (1:1wt).
[0016] Furthermore, the step S1 comprises:
[0017] Ethylene-vinyl alcohol polymer EVOH particles and a solvent are added into a round-bottom flask, and heated and stirred until completely dissolved to obtain a coating liquid; the coating liquid is colorless and transparent.
[0018] Furthermore, in the step S1, the heating temperature is 80-130° C., the stirring rate is 300-600 rpm, and the stirring time is 4-6 hours.
[0019] Furthermore, the step S2 comprises:
[0020] The coating liquid is placed in a vacuum oven at 30-70°C for degassing for 1.5-3 hours.
[0021] Furthermore, the coating tool used in step S3 includes: a scraper, a roller or a wire rod, and the thickness is 200-600 μm.
[0022] Furthermore, the coagulation bath is deionized water or anhydrous ethanol.
[0023] Furthermore, the temperature of the coagulation bath is 30-80° C., and the phase separation time is 0.5-3 hours.
[0024] Furthermore, the step S5 comprises:
[0025] The diaphragm is placed in a vacuum oven at 50-70° C. and dried for 8-10 hours to obtain a white EVOH microporous membrane; the thickness of the white EVOH microporous membrane is 30-200 μm, and the diameter of the micropores is between 0.5-40 μm.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. Excellent hydrophilicity: The microporous material prepared by the present invention significantly improves the hydrophilicity by introducing ethylene-vinyl alcohol copolymer (EVOH). The abundant hydroxyl groups in EVOH have good compatibility with water molecules, enabling the material to quickly absorb water and maintain a wet state, and is suitable for fields such as water treatment and environmental protection.
[0028] 2. Controllability of microporous structure: The present invention precisely controls the formation of microporous structure by adjusting the solvent type, solution concentration and phase separation conditions, thereby adjusting the pore size distribution and porosity of the material; the uniform microporous structure not only provides good permeability, but also ensures the mechanical strength and stability of the material.
[0029] 3. Excellent mechanical properties: The microporous material prepared by the present invention has good flexibility while maintaining high mechanical strength, so that it has reliable durability in a variety of application scenarios.
[0030] 4. Simple and efficient process: The present invention adopts the immersion-precipitation phase separation method, and a uniform microporous structure can be obtained through simple process steps. The process does not require additional binders and complex solvent systems, reduces processing steps and costs, and is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The present invention is a flow chart of a method for preparing a polymer microporous material;
[0032] Figure 2 The surface and cross-sectional morphology scanning electron microscope photos of Experiment 1, where a is the surface morphology and b is the cross-sectional morphology;
[0033] Figure 3 The surface and cross-sectional morphology scanning electron microscope photos of Experiment 2, where a is the surface morphology and b is the cross-sectional morphology;
[0034] Figure 4 The surface and cross-sectional morphology scanning electron microscope photos of Experiment 3, where a is the surface morphology and b is the cross-sectional morphology;
[0035] Figure 5 The surface and cross-sectional morphology scanning electron microscope photos of Experiment 4, where a is the surface morphology and b is the cross-sectional morphology;
[0036] Figure 6The surface and cross-sectional morphology scanning electron microscope photos of Experiment 5, where a is the surface morphology and b is the cross-sectional morphology;
[0037] Figure 7 The surface and cross-sectional morphology scanning electron microscope photos of Experiment 6, where a is the surface morphology and b is the cross-sectional morphology;
[0038] Figure 8 The surface and cross-sectional morphology scanning electron microscope photos of Experiment 7, where a is the surface morphology and b is the cross-sectional morphology;
[0039] Fig. 9 These are photos of the water contact angle measurements of the samples, where a is for Experiment 1, b is for Experiment 2, and c is for Experiment 3. DETAILED DESCRIPTION
[0040] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0041] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0042] Embodiment 1
[0043] See also Figure 1 , a method for preparing a polymer microporous material, specifically comprising the following steps:
[0044] Step S1: preparing a coating liquid based on ethylene vinyl alcohol polymer EVOH particles and a solvent;
[0045] Step S2: degassing the coating liquid;
[0046] Step S3: uniformly coating the deaerated coating liquid on the glass plate;
[0047] Step S4: placing the coated glass plate into a coagulation bath for phase separation, and removing the diaphragm;
[0048] Step S5: After the separator is completely dried, a white EVOH microporous membrane is obtained; it should be noted that the content of vinyl alcohol segments in the white EVOH microporous membrane is not less than 60%.
[0049] In this embodiment, specifically, step S1 includes:
[0050] Adding ethylene-vinyl alcohol polymer EVOH particles and a solvent into a round-bottom flask, and heating and stirring until completely dissolved to obtain a coating liquid; the coating liquid is colorless and transparent;
[0051] Specifically, in the actual preparation process, firstly, a proper amount of ethylene-vinyl alcohol polymer EVOH particles are weighed in a round-bottom flask, a proper amount of solvent is added, and heating and stirring are performed until the particles are completely dissolved to obtain a colorless and transparent coating liquid with a certain solid content;
[0052] The solid content of the coating liquid is 10-30%, and the solvent is one of DMSO, NMP or NPA / H2O (1:1wt); DMSO is the abbreviation of dimethyl sulfoxide, NMP is the abbreviation of nitrogen-methylpyrrolidone, and NPA is the abbreviation of n-propanol.
[0053] In this embodiment, specifically, in step S1, the heating temperature is 80-130° C., the stirring rate is 300-600 rpm, and the stirring time is 4-6 hours.
[0054] In this embodiment, specifically, step S2 includes:
[0055] The coating liquid is placed in a vacuum oven at 30-70°C for degassing for 1.5-3 hours.
[0056] In this embodiment, specifically, the coating tool used in step S3 includes: a scraper, a roller or a wire rod, etc., with a thickness of 200-600 μm.
[0057] In this embodiment, specifically, the coagulation bath is deionized water or anhydrous ethanol.
[0058] In this embodiment, specifically, the temperature of the coagulation bath is 30-80° C. to promote the formation of the microporous membrane; and the phase separation time is 0.5-3 hours.
[0059] In this embodiment, specifically, step S5 includes:
[0060] The membrane was placed in a vacuum oven at 50-70°C and dried for 8-10 hours to obtain a white EVOH microporous membrane.
[0061] The white EVOH microporous membrane prepared by the method of this embodiment has a thickness of 30-200 μm and has good mechanical properties and toughness; the diameter of its micropores is between 0.5-40 μm, so as to provide excellent permeability.
[0062] Embodiment 2
[0063] This embodiment is based on the preparation method of a polymer microporous material proposed in the first embodiment for actual preparation.
[0064] Experiment 1
[0065] Step S1: weigh 12 g of ethylene-vinyl alcohol polymer EVOH particles in a round-bottom flask, add 68 g of DMSO, heat and stir at 100° C. in an oil bath for 4 hours at a stirring speed of 500 rpm, and obtain a colorless and transparent coating liquid after the particles are completely dissolved;
[0066] Step S2: placing the coating liquid in a vacuum oven at 40° C. for degassing for 2 hours;
[0067] Step S3: using a scraper with a thickness of 250 μm, evenly coating the degassed coating liquid on the glass plate;
[0068] Step S4: placing the coated glass plate in deionized water at 60° C. for phase separation, and removing the separator after 1 hour;
[0069] Step S5: Place the diaphragm in a vacuum oven at 70°C and dry it completely to obtain a white EVOH microporous membrane. The surface and cross-sectional morphology of the membrane are shown in the scanning electron microscope photos. Figure 2 shown.
[0070] Experiment 2
[0071] Step S1: weigh 9 g of ethylene-vinyl alcohol polymer EVOH particles in a round-bottom flask, add 51 g of NPA / H2O (1:1wt) mixed solvent, heat and stir at 90°C in an oil bath for 5 hours at a stirring speed of 350 rpm, and obtain a colorless and transparent coating liquid after the particles are completely dissolved;
[0072] Step S2: placing the coating liquid in a vacuum oven at 40° C. for degassing for 1.5 hours;
[0073] Step S3: using a scraper with a thickness of 300 μm, evenly coating the degassed coating liquid on the glass plate;
[0074] Step S4: placing the coated glass plate in anhydrous ethanol at 60°C for phase separation, and removing the diaphragm after 2 hours;
[0075] Step S5: Place the diaphragm in a vacuum oven at 70°C and dry it completely to obtain a white EVOH microporous membrane. The surface and cross-sectional morphology of the membrane are shown in the scanning electron microscope photos. Figure 3 shown.
[0076] Experiment 3
[0077] Step S1: weigh 10 g of ethylene-vinyl alcohol polymer EVOH particles in a round-bottom flask, add 40 g of NMP, heat and stir at 110° C. in an oil bath for 3 hours at a stirring speed of 400 rpm, and obtain a colorless and transparent coating liquid after the particles are completely dissolved;
[0078] Step S2: placing the coating liquid in a vacuum oven at 40° C. for degassing for 2 hours;
[0079] Step S3: using a scraper with a thickness of 250 μm, evenly coating the degassed coating liquid on the glass plate;
[0080] Step S4: placing the coated glass plate in deionized water at 60° C. for phase separation, and removing the separator after 1 hour;
[0081] Step S5: Place the diaphragm in a vacuum oven at 70°C and dry it completely to obtain a white EVOH microporous membrane. The surface and cross-sectional morphology of the membrane are shown in the scanning electron microscope photos. Figure 4 shown.
[0082] Experiment 4
[0083] Step S1: weigh 12 g of ethylene-vinyl alcohol polymer EVOH particles in a round-bottom flask, add 36 g of DMSO, heat and stir at 100° C. in an oil bath for 4 hours at a stirring speed of 500 rpm, and obtain a colorless and transparent coating liquid after the particles are completely dissolved;
[0084] Step S2: placing the coating liquid in a vacuum oven at 40° C. for degassing for 2 hours;
[0085] Step S3: using a scraper with a thickness of 250 μm, evenly coating the degassed coating liquid on the glass plate;
[0086] Step S4: placing the coated glass plate in deionized water at 60° C. for phase separation, and removing the separator after 1 hour;
[0087] Step S5: Place the separator in a vacuum oven at 70° C. and obtain a white EVOH microporous membrane after complete drying.
[0088] Experiment 5
[0089] Step S1: weigh 9 g of ethylene-vinyl alcohol polymer EVOH particles in a round-bottom flask, add 51 g of NPA / H2O (1:1wt) mixed solvent, heat and stir at 90°C in an oil bath for 5 hours at a stirring speed of 350 rpm, and obtain a colorless and transparent coating liquid after the particles are completely dissolved;
[0090] Step S2: placing the coating liquid in a vacuum oven at 40° C. for degassing for 1.5 hours;
[0091] Step S3: using a scraper with a thickness of 300 μm, evenly coating the degassed coating liquid on the glass plate;
[0092] Step S4: placing the coated glass plate in anhydrous ethanol at 70° C. for phase separation, and removing the diaphragm after 2 hours;
[0093] Step S5: Place the separator in a vacuum oven at 70° C. and obtain a white EVOH microporous membrane after complete drying.
[0094] Experiment 6
[0095] Step S1: weigh 10 g of ethylene-vinyl alcohol polymer EVOH particles in a round-bottom flask, add 40 g of NMP, heat and stir at 110° C. in an oil bath for 3 hours at a stirring speed of 400 rpm, and obtain a colorless and transparent coating liquid after the particles are completely dissolved;
[0096] Step S2: placing the coating liquid in a vacuum oven at 40° C. for degassing for 2 hours;
[0097] Step S3: using a scraper with a thickness of 250 μm, evenly coating the degassed coating liquid on the glass plate;
[0098] Step S4: placing the coated glass plate in deionized water at 40° C. for phase separation, and removing the separator after 2 hours;
[0099] Step S5: Place the separator in a vacuum oven at 70° C. and obtain a white EVOH microporous membrane after complete drying.
[0100] Experiment 7
[0101] Step S1: weigh 12 g of ethylene-vinyl alcohol polymer EVOH particles in a round-bottom flask, add 68 g of DMSO, heat and stir at 100° C. in an oil bath for 4 hours at a stirring speed of 500 rpm, and obtain a colorless and transparent coating liquid after the particles are completely dissolved;
[0102] Step S2: placing the coating liquid in a vacuum oven at 40° C. for degassing for 2 hours;
[0103] Step S3: using a scraper with a thickness of 250 μm, evenly coating the degassed coating liquid on the glass plate;
[0104] Step S4: placing the coated glass plate in deionized water at 40° C. for phase separation, and removing the separator after 1 hour;
[0105] Step S5: Place the separator in a vacuum oven at 70° C. and obtain a white EVOH microporous membrane after complete drying.
[0106] The data of surface porosity, volume porosity, average pore size and volume density of the white EVOH microporous membranes prepared in the above 7 groups of experiments are shown in the table below.
[0107] Table 1 Data comparison of white EVOH microporous membranes prepared in the above 7 groups of experiments
[0108]
[0109] Depend on Figure 2-Figure 4 It can be seen that the EVOH microporous materials prepared in different solvent systems show significant differences in microporous morphology. The DMSO system is more likely to form a finger-like macroporous structure, while the NPA / H2O (1:1wt) and NMP systems tend to form a sponge-like microporous structure.
[0110] Please refer to Table 1. Figure 2 , Figure 5 By comparing Experiment 1 and Experiment 4, as the solid content of the coating liquid increases, the viscosity of the system increases, the phase separation mass transfer resistance increases, resulting in a decrease in the diffusion coefficients of the solvent and non-solvent, which significantly affects the porosity and skin density of the diaphragm. At low concentrations, the skin porosity is higher due to the faster diffusion rate; at high concentrations, the viscosity increases, the mass transfer is limited, the skin is denser, and the surface porosity and volume porosity of the material are reduced.
[0111] At the same time, the increase in coagulation bath temperature also has a certain impact on the diffusion coefficient and phase separation rate of the phase separation system, thereby affecting the microporous structure and porosity of the diaphragm, and the impact on different systems is different. Please refer to Table 1. Figure 2 , Figure 8 ,From Experiments 1 and 7, it can be known that the diffusion coefficient of the DMSO system increases at high temperature, the solvent-nonsolvent exchange is accelerated, and it is easy to form a macroporous structure and a high porosity;
[0112] Please refer to Table 1. Figure 3 , Figure 6 ,From Experiments 2 and 5, it can be seen that the diffusion coefficient of the NPA / H2O (1:1wt) system decreases with increasing temperature, but the surface porosity and volume porosity of the material only decrease slightly, and the pore diameter increases slightly with increasing temperature and the structure is uniform;
[0113] Please refer to Table 1. Figure 4 , Figure 7By comparing Experiment 3 and Experiment 6, it can be found that since the diffusion coefficient of the NMP system also shows a decreasing trend with increasing temperature, as the temperature increases, the surface and volume porosity of the material gradually increases, the pore size does not change much and is relatively uniformly distributed.
[0114] like Fig. 9 As shown, by testing the water contact angle of Experiments 1, 2, and 3, it can be found that the water contact angle of the polymer microporous material prepared by the method of the present invention is very small, which proves that the hydrophilicity of the material is relatively excellent. This is due to the rich hydroxyl groups brought by the vinyl alcohol segment in the ethylene-vinyl alcohol copolymer. Therefore, this polymer microporous material has a good prospect in the application of the hydrophilic field.
[0115] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
[0116] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.
Claims
1. A method for preparing a polymer microporous material, characterized in that: include: Step S1: preparing a coating liquid based on ethylene vinyl alcohol polymer EVOH particles and a solvent; Step S2: degassing the coating liquid; Step S3: coating the degassing coating liquid on the glass plate; Step S4: placing the coated glass plate into a coagulation bath for phase separation, and removing the diaphragm; Step S5: After the separator is completely dried, a white EVOH microporous membrane is obtained.
2. The method for preparing a polymer microporous material according to claim 1, characterized in that: The solid content of the coating liquid is 10-30%.
3. The method for preparing a polymer microporous material according to claim 1, characterized in that: The solvent is one of DMSO, NMP or NPA / H2O (1:1wt).
4. The method for preparing a polymer microporous material according to claim 1, characterized in that: The step S1 comprises: Ethylene-vinyl alcohol polymer EVOH particles and a solvent are added into a round-bottom flask, and heated and stirred until completely dissolved to obtain a coating liquid; the coating liquid is colorless and transparent.
5. The method for preparing a polymer microporous material according to claim 4, characterized in that: In the step S1, the heating temperature is 80-130° C., the stirring rate is 300-600 rpm, and the stirring time is 4-6 hours.
6. The method for preparing a polymer microporous material according to claim 1, characterized in that: The step S2 comprises: The coating liquid is placed in a vacuum oven at 30-70°C for degassing for 1.5-3 hours.
7. The method for preparing a polymer microporous material according to claim 1, characterized in that: The coating tool used in step S3 includes: a scraper, a roller or a wire rod, and the thickness is 200-600 μm.
8. The method for preparing a polymer microporous material according to claim 1, characterized in that: The coagulation bath is deionized water or anhydrous ethanol.
9. The method for preparing a polymer microporous material according to claim 8, characterized in that: The temperature of the coagulation bath is 30-80° C., and the phase separation time is 0.5-3 hours.
10. The method for preparing a polymer microporous material according to claim 1, characterized in that: The step S5 comprises: The diaphragm is placed in a vacuum oven at 50-70° C. and dried for 8-10 hours to obtain a white EVOH microporous membrane; the thickness of the white EVOH microporous membrane is 30-200 μm, and the diameter of the micropores is between 0.5-40 μm.
Citation Information
Patent Citations
Preparation method of high-flux hydrophilic microporous filtering film and application thereof
CN103071394A
Preparation method of enhanced flat composite microporous membrane for improving hydrophility
CN104248915A
Hydrophilic polyethylene microporous membrane and preparation method thereof
CN112044281A
Porous polymer membrane
JP2014200752A
Ethylene-vinyl alcoholic copolymer film and method for producing the same
JP2023170733A